Creating English Brochure for the Instagram of CV. Sahabat Nusantara Sejahtera Purwokerto - Fadilah, Royan; Mariasari, Septi; Purwandari, Gigih Ariastuti (Jurnal Vokasia, 2022)
The purposes of the article are to explain the process in creatinhg English promotion in Instagram at CV. Sahabat Nusantara Sejahtera Purwokerto, and to observe obstacles and find solution in creating an English promotion in Instagram at CV. Sahabat Nusantara Sejahtera Purwokerto. The method used are observation, practicing and interview. To make a brochure promotion several steps should be followed. First, determining what components would be included in the brochure. Second, taking photos directly at the tourist destination as material for making brochures. Third, editing the material according to the theme and ideas that has already determined. Fourth, consulting of the result was conducted to the supervisor and the owner of the company.